Endoscopic full-thickness resection using a clip non-exposed method for gastrointestinal tract lesions: a meta-analysis - Brewer Gutierrez, Olaya I.; Akshintala, Venkata S.; Ichkhanian, Yervant; Brewer, Gala G.; Hanada, Yuri; Truskey, Maria P.; Agarwal, Amol; Hajiyeva, Gulara; Kumbhari, Vivek; Kalloo, Anthony N.; Khashab, Mouen A.; Ngamruengphong, Saowanee (Endoscopy International Open, 2020)
Background and study aims Endoscopic full-thickness resection (EFTR) allows for treatment of epithelial and sub-epithelial lesions (SELs) unsuitable to conventional resection techniques. This meta-analysis aimed to assess the efficacy and safety of clip-assisted method for non-exposed EFTR using FTRD or over-the-scope clip of gastrointestinal tumors.Methods A comprehensive literature search was performed. The primary outcome of interest was the rate of histologic complete resection (R0). Secondary outcomes of interest were the rate of enbloc resection, FTR, adverse events, and post-EFTR surgery. Random-effects model was used to calculate pooled estimates and generate forest plots.Results Eighteen studies with 730 patients and 733 lesions were included in the analyses. Indications for EFTR were difficult/residual colorectal adenoma, adenoma at a diverticulum or appendiceal orifice and early cancer (n = 634), colorectal SELs (n = 42), and upper gastrointestinal lesions (n = 51), other colonic lesions (n = 6). Median size of lesions was 13.5 mm. There were 22 failed EFTR attempts. Pooled overall R0 resection rate was 82 % (95 % CI: 75, 89). The pooled overall FTR rate was 83 % (95 % CI: 77, 89). The pooled overall enbloc resection rate was 95 (95 % CI: 92, 96). The pooled estimates for perforation and bleeding were < 0.1 % and 2 %, respectively. Following EFTR, a total of 110 patients underwent surgery for any reason [pooled rate 7 % (95 % 2, 14). The pooled rates for post-EFTR surgery due to invasive cancer, for non-curative endoscopic resection and for adverse events were 4 %, < 0.1 % and < 0.1 %, respectively. No mortality related to EFTR was noted.Conclusions EFTR appears to be safe and effective for gastrointestinal lesions that are not amenable to conventional endoscopic resection. This technique should be considered as an alternative to surgery in selected cases.